Sexual, marital, and general life functioning in couples coping with colorectal cancer: a dyadic study across time. Issue 9 (20th March 2015) - Traa, Marjan J.; Braeken, Johan; De Vries, Jolanda; Roukema, Jan A.; Slooter, Gerrit D.; Crolla, Rogier M. P. H.; Borremans, Monique P. M.; Den Oudsten, Brenda L.
Abstract Objectives This study evaluated the following: (a) levels of sexual, marital, and general life functioning for both patients and partners; (b) interdependence between both members of the couple; and (c) longitudinal change in sexual, marital, and general life functioning and longitudinal stress‐spillover effects in these three domains from a dyadic perspective. Methods Couples (n = 102) completed the Maudsley Marital Questionnaire preoperatively and 3 and 6 months postoperatively. Mean scores were compared with norm scores. A multivariate general linear model and a multivariate latent difference score – structural equation modeling (LDS‐SEM), which took into account actor and partner effects, were evaluated. Results Patients and partners reported lower sexual, mostly similar marital, and higher general life functioning compared with norm scores. Moderate to high within‐dyad associations were found. The LDS‐SEM model mostly showed actor effects. Yet the longitudinal change in the partners' sexual functioning was determined not only by their own preoperative sexual functioning but also by that of the patient. Preoperative sexual functioning did not spill over to the other two domains for patients and partners, whereas the patients' preoperative general life functioning influenced postoperative change in marital and sexual functioning. Health care professionals should examine potential sexual problems but have to be aware that these problems may not spill over to the marital and general life domains. In contrast, low functioning in the general life domain may spill over to the marital and sexual domains. The interdependence between patients and partners implies that a couple‐based perspective (e.g., couple‐based interventions/therapies) to coping with cancer is needed. Copyright © 2015 John Wiley & Sons, Ltd.